THE ISSUE OF SOURCE SELECTION IN THE HISTORIOGRAPHY OF THE TIMURID PERIOD - Otayorova Hilola (Zamonaviy ilmiy yondashuvlar va texnologik taraqqiyotning ustuvor yo‘nalishlari, 2026)
This article analyzes the issue of source selection in the historiography of the Timurid period. The main written sources related to the Timurid era, their historical significance, scientific reliability, and degree of historical objectivity are examined. In addition, the issues of reconstructing historical truth through a comparative analysis of official and unofficial sources are highlighted.